SEARC Agricultural Research 2017 - L. W. Lomas (Kansas Agricultural Experiment Station Research Reports, 2017)
Southeast Agricultural Research Center, Agricultural Research 2017. Topics include grazing and supplemental feed for beef cattle, forage, pasture, hay, grasses, legumes, tillage, fertilizer, corn, soybeans, wheat, and soil health and variability.
Keywords: cattle; crops; forage